Oxidative stress–mediated photoactivation of carbazole inhibits human skin cell physiology. Issue 2 (10th November 2019) - Srivastav, Ajeet K.; Dubey, Divya; Chopra, Deepti; Singh, Jyoti; Negi, Sandeep; Mujtaba, Syed Faiz; Dwivedi, Ashish; Ray, Ratan Singh
Abstract: Prolonged exposure of the earth's surface to the sun's ultraviolet radiation may result in various skin diseases and cataract. Carbazole (CBZ), as a polycyclic‐aromatic hydrocarbon (PAH), is blended with a five‐member nitrogen‐containing ring. It is found in cigarette smoke, coal, eye kohl, tattoo ink, and wood combustion and affects various types of flora and fauna. Our findings suggest that CBZ generates reactive oxygen species (ROS) like O 2 − through type‐I photodynamic reaction and causes phototoxicity in the human keratinocyte cell line (HaCaT), which has been proved by mitochondrial dehydrogenase and neutral red uptake assays. CBZ induces single strand DNA damage. We have investigated the involvement of the apoptotic pattern of cell death and confirmed it by cytochrome C release from mitochondria and caspase‐9 activation. Similarly, photo‐micronuclei formation was associated to CBZ‐induced phototoxicity. The results of this study strongly support that the upregulation of bax, cyto‐C, apaf‐1, casp‐9 and down regulation of bcl2, keap‐1, nrf‐2, and hmox‐1 genes cause apoptopic cell death. Downregulation of antioxidant genes showed a significant amount of ROS generation by photosensitized CBZ. Therefore, the current study will be a step forward to safeguard human beings from sunlight‐induced photosensitive CBZ prolonged exposure. Abstract : Photosensitized carbazole showed morphological changes in HaCaT cells.